2007
DOI: 10.1002/hep.21806
|View full text |Cite
|
Sign up to set email alerts
|

Profibrogenic transforming growth factor-β/activin receptor–like kinase 5 signaling via connective tissue growth factor expression in hepatocytes

Abstract: Connective tissue growth factor (CTGF) is important for transforming growth factor-␤ (TGF-␤)-induced liver fibrogenesis. Hepatic stellate cells have been recognized as its major cellular source in the liver. Here we demonstrate the induction of CTGF expression in hepatocytes of damaged livers and identify a molecular mechanism responsible for it. CTGF expression was found by immunohistochemistry in bile duct epithelial cells, hepatic stellate cells, and hepatocytes in fibrotic liver tissue from patients with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 71 publications
3
102
1
Order By: Relevance
“…For example, CTGF is a cytokine induced by TGF-b that acts synergically to promote matrix protein deposition and fibrogenesis, both in vitro and in vivo. 34 Smad3 signaling has been identified as the responsible pathway inducing CTGF expression in hepatocytes of CCl 4 -treated mice, 35 and knockdown of CTGF by injection of small interfering RNA into the portal veins of rat livers prevents CCl 4 -induced fibrosis by inhibiting TGF-b induction and HSC activation. 36 It has been reported that in rats treated with CCl 4 silymarin decreases CTGF to improve liver fibrosis 37 and curcumin significantly attenuates the severity of liver damage through inhibition of CTGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CTGF is a cytokine induced by TGF-b that acts synergically to promote matrix protein deposition and fibrogenesis, both in vitro and in vivo. 34 Smad3 signaling has been identified as the responsible pathway inducing CTGF expression in hepatocytes of CCl 4 -treated mice, 35 and knockdown of CTGF by injection of small interfering RNA into the portal veins of rat livers prevents CCl 4 -induced fibrosis by inhibiting TGF-b induction and HSC activation. 36 It has been reported that in rats treated with CCl 4 silymarin decreases CTGF to improve liver fibrosis 37 and curcumin significantly attenuates the severity of liver damage through inhibition of CTGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…134 Although stimulation of CTGF production traditionally has been considered TGFβ-dependent, 135 TGFβ-independent regulation is increasingly likely as well. 136 Moreover, TGFβ stimulates CTGF primarily in hepatocytes, not stellate cells, 137,138 a notable exception to the general rule that cytokine signaling in stellate cell activation typically is autocrine.…”
Section: Perpetuating Pathwaysmentioning
confidence: 99%
“…Until recently CTGF was accepted to be expressed by activated stellate cells in liver diseases (Paradis et al, 2002). The involvement of CTGF in hepatocytes of hepatitis B virus infected livers as well as in CCL 4 treated mice (Weng et al, 2007) is a novel finding. It is noteworthy that expression of CTGF was mainly mediated by TGF-b ⁄ serine ⁄ threonine kinase receptor (ALK)5⁄ Smad3 signaling, although additional pathways have been described to contribute to TGF-b-mediated CTGF expression in other cells types (Arnott et al, 2008;Woods et al, 2008).…”
Section: Role Of Hepatocytes: Epithelial To Mesenchymal Transitionmentioning
confidence: 99%